2018
DOI: 10.1590/0001-3765201820150182
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Agaricus brasiliensis extract supplementation on honey bee colonies

Abstract: This study was done to discover any beneficial effect of a medicinal mushroom Agaricus brasiliensis extract on the honey bee. Firstly, a laboratory experiment was conducted on 640 bees reared in 32 singleuse plastic rearing cups. A. brasiliensis extract proved safe in all doses tested (50, 100 and 150 mg/kg/ day) irrespective of feeding mode (sugar syrup or candy). Secondly, a three-year field experiment was conducted on 26 colonies treated with a single dose of A. brasiliensis extract (100 mg/kg/day) added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…Bee colonies in the experiment were uniform regarding the number of frames, populations of adult bees and the quantity of stored food [29]. Throughout the experiment, the health of the colonies was checked on a reguar basis, as recommended by ОIE [30].…”
Section: Methodsmentioning
confidence: 99%
“…Bee colonies in the experiment were uniform regarding the number of frames, populations of adult bees and the quantity of stored food [29]. Throughout the experiment, the health of the colonies was checked on a reguar basis, as recommended by ОIE [30].…”
Section: Methodsmentioning
confidence: 99%
“…The use of supplements with sugar syrup should not be avoided, since they provide suffi cient amino acids, peptides, micro-and macroelements which are absent from pure sugar syrup [18]. The use of supplements may prevent energetic, immune and oxidative stress in bees, and thus prevent losses in apiaries [129,[171][172][173][174]. The presence of a young, healthy bee queen in the hive guarantees the development of healthy bee colonies and successful beekeeping [131,175].…”
Section: General Management In the Apiarymentioning
confidence: 99%
“…Moreover, its effectiveness has been questioned [28], imposing a constant effort of scientists to discover alternative substances, which would be effective against Nosema spp. Among many natural compounds tested [5,[36][37][38][39][40][41][42][43][44][45][46][47], some of them showed promising anti-Nosema effects such as algae and fungus extracts [5,22,[36][37][38][39], chitosan and peptidoglycan [40], naringenin, sulforaphane and carvacrol [41], probiotics [42,46], natural substances from Brassicaceae defatted seed meals [43], and natural-based commercial formulations [5,44,47,48]. Diet with the addition of plant-based, amino acid and vitamin supplements, led to reduction of N. ceranae spore number [5,48], immunostimulation, and reduction of oxidative stress in N. ceranae-infected bees [5], and consequently to the improved condition of bees.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in mushrooms has been increasing among researchers due to their nutritional and medicinal properties; mushrooms of the genus Agaricus contain numerous biologically-active substances (such as glucans, mannan, lentinan, schizophyllan, scleroglucan) with certain antitumor, antidiabetic, and immunostimulatory effects [49][50][51][52][53][54][55][56]. Stevanovic et al [38] observed a favorable effect of A. blazei extract on the strength parameters of bee colonies in a field experiment, while Glavinic et al [5] revealed the positive effect of A. blazei extract in laboratory experiment. The extract stimulated the expression of genes important for immunity, reducing oxidative stress caused by N. ceranae and consequently reducing N. ceranae infection.…”
Section: Introductionmentioning
confidence: 99%